Caracterização físico-química de biomateriais para enxerto ósseo de origem alógena e xenógena - Dalapicula, Sabrina Serrão (2007)
The biomaterials have been widely used in Implantology. The act in the procedures Of reconstruction of ridge alveolar, totally or partially, lost as a consequence of Periodontal diseases, traumatic extractions, cists, tumors and traumatisms. The Behavior in vitro of these biomaterials is highly dependent of its chemical and Physical characteristics proprieties, which can be estimated through tests in vitro. The Understanding of the main chemical and physical characteristics of these Biomaterials, witch include the namely crystallinity, the specific superficial area and The chemical composition, allows the professional from the health area, to choose the Most appropriate material for one specific clinical application. However the criteria to A production and commercialization of these biomaterials for bone grafts are not Defined by responsible regulation agencies causing a lack control of the materials Used in human beings. The aim of work was to characterize six biomaterials of Bone grafts five xenogeny origin and of halogen origin. Physicochemical Characterization was corried out by using electron microscopy (SEM), X-ray, Diffraction (XRD), surface area (BET) measurement and crystallinity of sample. The Result reported that all the samples, except the D, were constituted of hydroxyapatite With different intensities of carbonate incorporation, with different grain size bands, Area of surface varying of 0,18 to 81,4 and crystallinity varying of low to high, Demonstrating that although the similarity of its compositions the analyzed Biomaterials present a big difference of chemical and physical parameters.